Character Building in Language Teaching: An Analysis of the Learning Activities - Mohammad Ilyas (Script Journal: Journal of Linguistics and English Teaching, 2020)
This study was aimed to describe how implement character building in language teaching (Indonesia and English) at Junior High School. An examination of relevant documents, in addition to observations and interviews, was used to compile the data. According to the findings of this research, the six different lesson plans that were analyzed contained a total of 12 different character values. The character values were reinforced upon by two different teachers throughout the various learning activities, and they were mentioned in a special sub-title as well. Based on the findings, it appears that only teacher A taught the character qualities by directly stating them to the students. The lessons on values were typically integrated into the activities that were being done by the other two teachers.